Children's bone health - Sluis, Inge Margriet van der (nakladatel není známý, 2002)
The publication focuses on bone mineral density and bone mineral density diseases in children and adolescents. Written for professional public.
Keywords: mladiství; Child; Bone Density; komorbidita; dítě; osteologie; kosti a kostní tkáň; Comorbidity; Bone Diseases, Metabolic; pediatrie; metabolické nemoci kostí; Bone and Bones; kostní denzita; Adolescent